Avaliação morfofuncional do manguito rotador em indivíduos com instabilidade glenoumeral e lesão SLAP - Saccol, Michele Forgiarini (Universidade Federal de São Carlos, 2013)
Athlete´s shoulder most frequent lesions are anterior shoulder instability and superior labrum anterior and posterior lesion ( SLAP), altering structures and functions of the shoulder joint, leading to impairments in sports activity. The aim of this thesis was to evaluate functional and supraspinatus morphological adaptations of shoulder in athletes with anterior instability and SLAP lesion. Three studies were developed. The first study investigated functional differences regarding clinical complaints and the scoring systems of American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) and the Athletic Shoulder Outcome Rating Scale (ASORS) in 249 athletes (153 with instability and 96 with SLAP lesion). The groups presented functional differences related mainly to sports activitiy and, even with more complaints of shoulder pain, SLAP lesion athlete´s tolerate more training hours compared to instability athletes. The second study evaluated isokinetic strenght and muscular control of shoulder rotators in four groups: instability group (n=10), instability control group (n=10), SLAP group (n=10) and SLAP control group (n=10). The torque steadiness and rotator cuff strength in 90 and 180°/s were evaluated. Athlete´s with anterior stability presented shoulder rotation weakness, while athletes with SLAP lesion showed higher torque fluctuation of shoulder internal rotation. The third study characterized the different fiber types of supraspinatus and shoulder function in those lesions. This study performed muscles biopsies in 10 athletes undergoing to arthroscopy repair of shoulder anterior instability and SLAP lesion. The volunteers were functionally evaluated with ASES and ASORS, and muscle samples were processed with histochemical reaction for myosin adenosine triphosphatase (mATPase). Muscles fibers were then characterized in type I, IIa, IIb and hybrid, and percentual and lesser diameter of each fiber type were calculated. In this study, volunteers presented evident functional limitations in sports activity and hypertrophy of all typees of muscles fibers. Most of the sample also presented a great number of type IIa and IIb in the supraspinatus muscle. In conjuction, those studies proves different functional and supraspinatus morphologic adaptations in athletes with anterior shoulder instability and SLAP lesion, justifying the need of different rehabilitations approaches.
Keywords: Articulações; Ombro; Atletas; Questionários; Força muscular; Biópsia muscular; Instabilidade articular; Lesão SLAP; Desempenho neuromuscular; Bainha rotadora; Músculo supraespinhoso; Shoulder; Joint instability; SLAP lesion; Athletes; Questionnaires; Muscle strength; Sensorimotor control; Rotator cuff; Biopsy; Supraspinatus muscle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL